Development of strain sensor using conductive poly(vinylidene fluoride) (PVDF) nanocomposite membrane reinforced with ionic liquid (IL) & carbon nanofiber (CNF). (15th September 2019) - Prasad, Brijesh; Gill, Fateh Singh; Panwar, Varij; Anoop, Gopinathan
Abstract: High sensitivity and good mechanical strength are required for conductive polymer nano-composites (CPNC) based flexible strain sensors. Here we have developed CPNC membranes using PVDF as a base polymer along with carbon nanofiber (CNF) and ionic liquid (IL) as conducting fillers exhibiting good thermal stability, high sensing voltage, and mechanical performance for strain sensors. The IL infiltration in PVDF and CNFs composition resulted in micro-porous morphology that exhibited stretchability (maximum elongation = 5.8 mm) and a high gauge factor (4.08) (property of a good strain sensor). Further, infiltration of IL in PVDF/CNF membrane brings microstructural changes (α to β phase) of PVDF and provides an electrolyte mixture of CNF and IL for the facile flow of ions through it. The CNFs in CPNC having IL helped in maintaining the crack initiation during strain. Hence, the deformed CNFs across the pores or within the PVDF act as an interlinking agent and provides an electrical conduction pathway in the shrink lattice of the composite.